Produtivity of organic coffee orchard in the brazilian savannah after prunning and grown under different water regimes - Nascimento, Luís Marques do; Spehar, Carlos Roberto; Sandri, Delvio (Coffee Science - ISSN 1984-3909, 2014)
Pruning has been a form of coffee orchard renewal with lesser cost than its eradication followed by a new planting. This experiment aimed at evaluating the effect of water regimes and predetermined stress on productivity of high density organic coffee orchard (7,142 plants ha-1), cv. IAPAR 59, after pruning. The water regimes were: rain fed no irrigation (control), continuous irrigation, water suppression 30 days before harvest, suppression at harvest and suppression at harvest associated with stem conduction. The experimental design was a complete randomized block, where water regimes were the treatments, with six repetitions. Yield per plot and per plant were evaluated in 2011; in 2012, the fruits were subdivided in cherry, cherry and green, dry and floating, in addition to biennial and accumulated yield evaluations. In the first year after pruning there was no coffee production. Three years after, however, in 2012, yield was restored. The treatments with programmed irrigation stops had increased yields, overcoming the non-irrigated treatment. Continuous irrigation reduced the proportion of dry and floating fruits, although increased the proportion of green fruits. Stem conduction after pruning increased the proportion of cherry, with less dry and floating fruits. Suppression at harvest associated with stem conduction was effective on plant, biennial, and accumulated yields.